Energy and security in South Asia cooperation or conflict? - Ebinger, Charles K. (Washington, D.C. Brookings Institution Press, 2011)
"Argues that mistrust, ethnic and religious sectarianism, and political parochialism among the nations of South Asia, a region of strategic geopolitical importance, prevent the region from achieving energy security, which is crucial for economic development and political stability. Recommends measures to improve energy security through domestic policy reform and more effective bilateral and multilateral cooperation"--Provided by publisher.
Introduction to a region on edge -- India -- Pakistan -- Bangladesh -- Nepal and Bhutan -- Energy challenges in the regional context -- Regional cooperation -- South Asia's path forward -- Appendix. Origins of the U.S.-India nuclear deal.
Keywords: Power resources -- Asia, South; Energy policy -- Asia, South; Energy security -- South Asia